Some Remarks About Heisenberg Groups (Journal of Partial Differential Equations, 2002)
In this paper, we give two inequalities and another characterizations about Heisenberg groups which do not coincide with the related results in classical case.
Keywords: Heisenberg Group; weakly-compactness; curvature; metric differentiability